Astronauts - Becklake, Sue; Reeves, Pauline (Essex Miles Kelly Publishing Ltd, 2021)
This humorous twist on the popular Q & A format takes a sideways look at all that is intriguing and fascinating about astronauts. Quirkily illustrated characters and playful text reveal the amazing answers. Find out who does the housework on the ISS, why spacesuits have gold visors, and how long space sickness lasts
Famous People
Keywords: inventors